Evaluation Of The Anti-Hyperlipidaemic Activity Of Premna Integrifolia On Nicotine Induced Hyperlipidaemia In Rats - MANISH J. PATEL; DR J.K. PATEL (International Journal of Pharma and Bio Sciences, 2012)
Nicotine caused significant increase in the serum Cholesterol, Triglyceride, VLDL, LDL & significant reduction in HDL level. Premna integrifolia & Atorvastatin treatment showed significant prevention in increased serum Cholesterol, Triglyceride, LDL as compared to Nicotine control (NC) group. While HDL level was significantly increased in treated & standard group as compared to Nicotine control (NC) group. Materials and methods used for research are as: male albino rats weighing 200-250 gm were divided into 4 groups viz. Normal control; Nicotine control (NC); Nicotine control (NC) & Premna integrifolia (Agnimantha) (500 mg/ kg) treated; Nicotine control (NC) & Atorvastatin treated (standard control). Blood samples were collected after 7 days, for lipid estimation. From the above results we conclude that Premna integrifolia is effective as an anti-hyperlipidemic agent.